2020
DOI: 10.3390/atmos11020153
|View full text |Cite
|
Sign up to set email alerts
|

Warm Island Effect in the Badain Jaran Desert Lake Group Region Inferred from the Accumulated Temperature

Abstract: The Badain Jaran Desert (BJD) is characterized by the coexistence of over 110 perennial lakes and thousands of megadunes in its southeast part. Unlike the cold island effect, we found a special phenomenon of the warm island effect in the lake group region of the BJD. However, the concept and formation mechanism remains unclear. In this study, based on observations of land surface processes in the area, we first used the daily mean temperature from 23 automated meteorological stations from 2010 to 2017 to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Thus, this is regarded as the study area in the lake area, and the lake area is defined with a 10 km buffer zone from the lakes. Furthermore, the lake area is a blend of surfaces (both water and land) [9,12]. The northern part of the desert has fewer lakes than other areas [25]; Thus, the non-lake area is defined as the northern desert area adjacent to the lake-group region (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, this is regarded as the study area in the lake area, and the lake area is defined with a 10 km buffer zone from the lakes. Furthermore, the lake area is a blend of surfaces (both water and land) [9,12]. The northern part of the desert has fewer lakes than other areas [25]; Thus, the non-lake area is defined as the northern desert area adjacent to the lake-group region (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The lake surface reflectance is smaller than that of the land surface; the radiation absorbed by the water surface is more than the net radiation absorbed by the land surface which is confirmed. Liang et al (2020) analysed the annual variation characteristics of monthly net radiation from both land and lake stations in the hinterland of the BJD (Figure 8); they found that the net radiation at the lake station (E1) was much higher than that of the land station (E2). The total annual net radiation of the E1 station (2937.5 MJ/m 2 ) was more than twice that of the E2 station (1340.3 MJ/m 2 ); the difference was larger in summer and smaller in winter [11].…”
Section: Reasons For the Warm Island Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research in the Badain Jaran Desert (BJD) in China have reported air temperatures in the lake areas to be significantly higher than in the surrounding region and as a result, the 'warm island effect' concept was introduced. Zhang et al (2015) and Liang et al (2020) have shown that the winter surface air temperature and accumulated air temperature in the BJD lake area are higher than those in surrounding areas. This may be related to the deep groundwater which recharges the lakes.…”
Section: Introductionmentioning
confidence: 96%